Creating the necessary infrastructure for a trauma-informed system of care for children and youth - Lyons, John S.; Fernando, April D. (Frontiers in Psychology, 2023)
Understanding and addressing the impact of adverse life events is an important priority in the design of helping systems. However, creating trauma-informed systems requires efforts to embed an effective trauma-informed work in routine practice. This paper discusses a model for developing trauma-informed systems using the Transformational Collaborative Outcomes Management (TCOM) framework, a strategy for engineering person-centered care. Person-centered care is naturally congruent with trauma-informed care. We describe the initial stages of implementation of a trauma-informed standardized assessment process to support the sustained evolution of a trauma informed care. Distinguishing between traumatic experiences and traumatic stress is fundamental to an effective trauma-informed system. We describe two sets of analyses—one in a statewide child welfare system and the other in a statewide behavioral health system. These projects found opportunities in the analysis of detection of traumatic stress based on traumatic experiences to inform practice and policy. Being trauma-informed in child welfare is distinct to being trauma-informed in behavioral health. In child welfare, it appears that a number of children are resilient in the face of traumatic experiences and do not require trauma treatment interventions. However, delayed and missed traumatic stress responses are common. In behavioral health, misses often occur among adolescents, particularly boys, who engage in acting out behavior. Opportunities for the ongoing development of trauma-informed systems using the TCOM framework are discussed.